Development and Optimization of Solanum Lycocarpum Polyphenol Oxidase-Based Biosensor and Application towards Paracetamol Detection - Rafael Souza Antunes; Douglas Vieira Thomaz; Luane Ferreira Garcia; Eric de Souza Gil; Flavio Marques Lopes (Tabriz University of Medical Sciences, 2021)
Purpose: The development biosensing technologies capable of delivering fast and reliable analysis is a growing trend in drug quality control. Considering the emerging use of plant-based polyphenol oxidases (PPO) as biological component of electrochemical biosensors, this work reports the first Solanum lycocarpum PPO biosensor and its use in the pharmaceutical analysis of paracetamol in tablet formulations. Methods: The biosensor was optimized regarding fruit maturation (immature and mature-ripe), vegetal extract volume to be used in biosensor construction as well as optimal pH of electrochemical cell fluid. Results: Results evidenced that the extract which rendered the biosensor with best analytical performance was from immature fruits, and the biosensor produced using 100 µL of crude plant extract promoted better faradaic signal gathering. Moreover, when neutral pH media was used in the electrochemical cell, the biosensor showcased best faradaic signal output from the used redox probe (catechol), suggesting thence that the method presents high sensibility for phenolic compounds detection. Furthermore, the biosensor was able to quantify paracetamol in a linear range from 50 to 300 μM, showcasing LoD and LoQ of 3 μM and 10 μM, respectively. Conclusion: after careful evaluation, this biosensor might be a low-cost alternative for conventional pharmaceutical quality control methods.